2004
DOI: 10.1128/ec.3.4.944-954.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Forkhead Transcription Factor Fkh2 Regulates the Cell Division Cycle of Schizosaccharomyces pombe

Abstract: In eukaryotes the regulation of gene expression plays a key role in controlling cell cycle progression. Here, we demonstrate that a forkhead transcription factor, Fkh2, regulates the periodic expression of cdc15 ؉ and spo12 ؉ in the M and G 1 phases of the cell division cycle in the fission yeast Schizosaccharomyces pombe. We also show that Fkh2 is important for several cell cycle processes, including cell morphology and cell separation, nuclear structure and migration, and mitotic spindle function. We find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 54 publications
6
54
0
1
Order By: Relevance
“…It is involved in septum formation, cytokinesis, nuclear structure and mitotic spindle function (Bulmer et al, 2004). It was also suggested that Fkh2 was implicated in the periodic gene expression of M and G1 phases (Buck et al, 2004), (when it is phosphorylated (Buck et al, 2004)) by negatively regulating the transcription of a cluster of genes (Rustici et al, 2004).…”
Section: Forkhead Transcription Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is involved in septum formation, cytokinesis, nuclear structure and mitotic spindle function (Bulmer et al, 2004). It was also suggested that Fkh2 was implicated in the periodic gene expression of M and G1 phases (Buck et al, 2004), (when it is phosphorylated (Buck et al, 2004)) by negatively regulating the transcription of a cluster of genes (Rustici et al, 2004).…”
Section: Forkhead Transcription Factorsmentioning
confidence: 99%
“…It was also suggested that Fkh2 was implicated in the periodic gene expression of M and G1 phases (Buck et al, 2004), (when it is phosphorylated (Buck et al, 2004)) by negatively regulating the transcription of a cluster of genes (Rustici et al, 2004). The null mutant displays longer length, coldsensitive, heat-sensitive and slow-growing phenotypes (Buck et al, 2004), (Bulmer et al, 2004). Regarding meiosis, a null mutant presents low levels of ste11 mRNA, dephosphorylation at Fkh2 residues T314 and S462 is required for binding to ste11 promoter region and induction of ste11 transcription during nitrogen starvation (Shimada et al, 2007).…”
Section: Forkhead Transcription Factorsmentioning
confidence: 99%
“…Protein extracts were prepared as described previously using lysis buffer (50 mM Tris-HCl pH 7.5, 150 mM NaCl, 0.5% Nonidet P-40, 10 mM imidazole, 0.1% leupeptin, 0.1% pepstatin A, 1% aprotinin, 1% phenylmethylsulfonyl fluoride, 0.2% Na 3 VO 4 , 5% NaF). 33 Proteins to be in MBF-dependent gene expression occurs in yox1Δ cells treated with HU and, significantly, both Rad3 and Cds1 are essential for replication stress-induced phosphorylation of Yox1. Since the timing of Rad3/Cds1-dependent phosphorylation of Yox1 coincides with the upregulation of MBF-dependent gene expression, we suggest that this phosphorylation of Yox1 is essential for dissociation of Yox1 from MBF target promoters and activation of gene expression (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Cultures were grown and extracts prepared using lysis buffer (50 mM TRIS-HCl pH 7.5, 150 mM NaCl, 0.5% Nonidet P-40, 10 mM imidazole, 0.1% leupeptin, 0.1% pepstatin A, 1% aprotinin, 1% PMSF, 0.2% Na 3 VO 4 , 5% NaF). 31 Protein samples were then analyzed by SDS-PAGE and transferred onto a nitrocellulose transfer membrane (Protran ® ). To investigate autophagic activity, the levels of Atg8-GFP and free GFP were examined using a 1:2,000 dilution of mouse anti-GFP antibody (Invitrogen) and a 1:2,000 dilution of anti-mouse HRP-conjugated secondary antibody (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…To analyze microtubules in mitotic cells, cells were fixed and prepared for microscopy as described previously. 31 To visualize microtubules, a 1:1,000 dilution of anti-TAT1 antibody (Cancer Research UK) and a 1:200 dilution of secondary antibody [Alexa Fluor ® FITC-conjugated anti-mouse antibody (Invitrogen)] were used for indirect immunofluorescence. Cells were mounted onto poly-L-lysine-coated microscope slides with Vectashield mounting medium (containing DAPIVector Laboratories).…”
Section: Methodsmentioning
confidence: 99%